Neoplasias cerebrales en pacientes sometidos a cirugía en el Hospital Isidro Ayora de Loja periodo 2013-2017 - Riofrío Trelles, Evelyn Janeth (2021)
Intracranial tumors in adults occupy the seventh place among neoplastic pathologies. In contrast, they constitute the second most frequent group of neoplasms after leukemia in children; its result is determined by the type, grade, and location of the tumor. The present study aimed to identify the prevalence of brain neoplasms according to sex and age group; know its anatomical location, and, know the type of tumor and the grade according to the histopathological study in patients undergoing surgery at the Hospital Isidro Ayora de Loja period 2013-2017. A retrospective cross-sectional study was developed with a quantitative approach, using the data collection form as a statistical tool, which facilitated obtaining information from the medical records of patients undergoing surgery, achieving the following results: the prevalence of brain neoplasms was 41 cases, of which 56,10% (n = 23) correspond to the female sex and 43,90% (n = 18) to the male sex. The group of patients was 40-65 years old with 39,02% (n = 16) of higher prevalence. The most frequent anatomical location of the tumors was in the parietal lobe with 34,15% (n = 14). The predominant type of tumor developed was astrocytoma 43,90% (n = 18) and the histological grade was grade I 20,51% (n = 8). The number of cases of brain tumors was higher in women, with a tendency to appear in adulthood and adolescence. Key words: tumor, pathologies, histopathological